Pengembangan Wilayah untuk Pembangunan Daerah Pangalengan Kabupaten Bandung Berbasis pada Satuan Genetik Wilayah Geologi dan Kebencanaan - Dudi Nasrudin Usman; Sri Widayati; Sriyanti Sriyanti (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
Unit of Area Genetics (SGW) as one of the methods in considering geological aspects for geologicarea-based development. The geological condition as part of the natural movement in a particularcondition makes it possible to predict its effect on the movement of an area in particular with regard tonatural disasters. Pangalengan who has a million beautiful natural charm, especially from the point ofpan-dang geology need it to be studied based on geological data. The charm is the presence of activevolcanoes in the region such as Mount Malabar, Mount Wayang, Mount Windu and others. In addition,the morphology of Pangalengan is relatively well represented in the highlands, hills and mountainareas as part of Java's tectonic activity. Another evidence of such activity is the existence of fault linesin the Pan-galengan mountains of Southeast-Northwest. Pangalengan who has a million beautifulnatural charm, especially from the point of pan-dang geology need it to be studied based on geologicaldata. The charm is the presence of active volcanoes in the region such as Mount Malabar, MountWayang, Mount Windu and others. In addition, the morphology of Pangalengan is relatively wellrepresented in the highlands, hills and mountain areas as part of Java's tectonic activity. Anotherevidence of such activity is the existence of fault lines in the Pan-galengan mountains of Southeast-Northwest.